Human biomonitoring initiative (HBM4EU): Human biomonitoring guidance values (HBM-GVs) derived for cadmium and its compounds. (February 2021) - Lamkarkach, Farida; Ougier, Eva; Garnier, Robert; Viau, Claude; Kolossa-Gehring, Marike; Lange, Rosa; Apel, Petra
Highlights: Derivation of Human Biomonitoring Guidance values (HBM-GVs) for Cadmium. Recommendation of HBM-GVs for the general population and workers. Methodology agreed according to the Human Biomonitoring Initiative (HBM4EU) project. Two specific biomarkers of cadmium exposure: urinary cadmium and blood cadmium. HBM-GVs aim to improve chemical risk assessment or health impact assessment. Abstract: Aims: The methodology agreed within the framework of the HBM4EU project is used in this work to derive HBM-GVs for the general population (HBM-GVGenPop ) and for workers (HBM-GVWorker ) exposed to cadmium (Cd) and its compounds. Methods: For Cd, a significant number of epidemiological studies with dose–response relationships are available, in particular for kidney effects. These effects are described in terms of a relation between urinary Cd (U-Cd) or blood Cd (B-Cd) levels and low molecular weight proteinuria (LMWP) markers like beta-2-microglobulin (β2M) and retinol-binding protein (RBP). In order to derive HBM-GVs for the general population and workers, an assessment of data from evaluations conducted by national or international organisations was undertaken. In this work, it appeared relevant to select renal effects as the critical effect for the both groups, however, differences between general population (including sensitive people) and workers (considered as an homogenous population of adults who should not be exposed to Cd if they suffer from renal diseases) required the selection of different key studies (i.e. conducted in general population for HBM-GVGenPop and at workplace for HBM-GVWorker ). Results and conclusions: For U-Cd, a HBM-GVGenPop of 1 µg/g creatinine (creat) is recommended for adults older than 50 years, based on a robust meta -analysis performed by EFSA (EFSA, 2009a ). To take into account the accumulation of Cd in the human body throughout life, threshold or 'alert' values according to age were estimated for U-Cd. At workplace, a HBM-GVWorker of 2 μg/g creat is derived from the study of Chaumont et al., (2011) for U-Cd, and in addition to this recommendation a HBM-GVworker for B-Cd of 5 µg/L is also proposed. The HBM-GVWorker for U-Cd is similar to the biological limit value (BLV) set by the new amendment of the European Carcinogens and Mutagens Directive in June 2019 (2 µg/g creat for U-Cd).